Peningkatan Kompetensi Literasi Digital Siswa Pada Pembelajaran PAI di SMP Negeri 1 Percut Sei Tuan - Damanik, Dea Yolanda; Al Farabi, Muhammad (Universitas Negeri Malang, 2023)
Abstract: The purpose of this study is to characterize how digital literacy competency has increased among students at SMP Negeri 1 Percut Sei Tuan in PAI learning. Three areas are the focus of this research study: strategies for raising students' digital literacy competency in PAI learning, the efforts of PAI teachers to raise students' digital literacy competency in PAI learning, and factors that facilitate or obstruct students' growth in digital literacy competency in junior high school PAI learning. Percut Sei Tuan Negeri 1. Qualitative descriptive research methodology was employed in this study. In this study, document analysis, interviews, and observation were the methods employed for gathering data. The results of this research explain that as time goes by, PAI teachers must broaden their perspective regarding the roles that need to be taken in carrying out the educational process for their students. The learning process that occurs today cannot only be done in the classroom but can be done without limits. Therefore, the PAI teacher's job is not to prohibit students from gaining knowledge from outside the classroom, but rather to facilitate and guide students so that they are able to maximize the development of information as a means of obtaining knowledge while still upholding religious values.Keywords: Islamic Religious Education, Digital Literacy, Technology Abstrak: Tujuan penelitian ini untuk mengetahui bagaimana peningkatan kompetensi literasi digital pada siswa SMP Negeri 1 Percut Sei Tuan dalam pembelajaran PAI. Ada tiga hal yang menjadi fokus kajian penelitian ini, yaitu strategi peningkatan kompetensi literasi digital siswa dalam pembelajaran PAI, upaya guru PAI dalam meningkatkan kompetensi literasi digital siswa dalam pembelajaran PAI, dan faktor-faktor yang memudahkan atau menghambat tumbuh kembang siswa dalam literasi digital. kompetensi pembelajaran PAI SMP. Percut Sei Tuan Negeri 1. Metode penelitian deskriptif kualitatif digunakan dalam penelitian ini. Dalam penelitian ini, analisis dokumen, wawancara, dan observasi merupakan metode yang digunakan untuk mengumpulkan data. Temuan penelitian ini memperjelas bahwa guru PAI perlu memiliki pandangan yang lebih luas tentang peran yang perlu dimainkan dalam menyelesaikan pendidikan siswanya seiring berjalannya waktu. Proses pembelajaran saat ini tidak terbatas pada ruang kelas saja; itu bisa terjadi di mana saja. Oleh karena itu, peran guru PAI bukanlah melarang siswa belajar di luar kelas; melainkan untuk mendukung dan membimbing siswa agar mereka dapat memanfaatkan kemajuan teknologi informasi sebagai alat untuk memperoleh pengetahuan dengan tetap menjaga prinsip-prinsip agama.Kata kunci: Pendidikan Agama Islam, Literasi Digital, Teknologi